2023
DOI: 10.1093/mrcr/rxad065
|View full text |Cite
|
Sign up to set email alerts
|

Solitary recurrence of IgG4-related giant coronary aneurysm: Case report and review of the literature focusing on treatment strategies and complications

Hiroyuki Kawahara,
Ichiro Mizushima,
Yasushi Matsumoto
et al.

Abstract: Coronary periarteritis is a dangerous manifestation of IgG4-related disease, because it forms coronary artery aneurysms, which may cause sudden cardiac death. We report the case of a 78-year-old woman with IgG4-related coronary periarteritis and a coronary aneurysm, which showed progressive enlargement despite maintenance therapy for Type 1 autoimmune pancreatitis. This case was unique, in that coronary periarteritis was the only active lesion that recurred. Low-dose glucocorticoids suppressed the progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Matsumoto et al 25 reported many cases with coronary periarteritis and/or aneurysm. Literature reviews by Akiyama et al 26 and Kawahara et al 27 reported that patients with IgG4-related coronary artery involvement often exhibited stenotic lesions (54-67% of patients), aneurysmal lesions (42-43%), and diffuse wall thickening (92-96%). Glucocorticoid treatment, either alone or in combination with percutaneous coronary intervention or cardiac surgery, has proven effective in managing most cases of IgG4-related coronary artery involvement.…”
Section: Proposal Of Revised 2023 Diagnostic Criteria For Igg4-relate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Matsumoto et al 25 reported many cases with coronary periarteritis and/or aneurysm. Literature reviews by Akiyama et al 26 and Kawahara et al 27 reported that patients with IgG4-related coronary artery involvement often exhibited stenotic lesions (54-67% of patients), aneurysmal lesions (42-43%), and diffuse wall thickening (92-96%). Glucocorticoid treatment, either alone or in combination with percutaneous coronary intervention or cardiac surgery, has proven effective in managing most cases of IgG4-related coronary artery involvement.…”
Section: Proposal Of Revised 2023 Diagnostic Criteria For Igg4-relate...mentioning
confidence: 99%
“…Glucocorticoid treatment, either alone or in combination with percutaneous coronary intervention or cardiac surgery, has proven effective in managing most cases of IgG4-related coronary artery involvement. However, 46% of cases with coronary artery aneurysm showed worsening of the outer diameter of the coronary aneurysms, 27 underscoring the importance of establishing an appropriate diagnosis and treatment strategy. In the present study, the revised diagnostic criteria for IgG4-related cardiovascular/retroperitoneal disease demonstrated an acceptable sensitivity and specificity for the diagnosis of patients with coronary artery lesions.…”
Section: Proposal Of Revised 2023 Diagnostic Criteria For Igg4-relate...mentioning
confidence: 99%